Evaluating the Sleep Treatment Education Program (STEP-1): A single-session educational workshop addressing insomnia in cancer survivors. Issue 1 (2nd January 2023) - Chevalier, Lydia L.; Fine, Elizabeth; Sharma, Aditi; Zhou, Eric S.; Recklitis, Christopher J.
Abstract: Insomnia is a common late effect of cancer, affecting as many as 27% of cancer survivors. Although cognitive behavioral therapy for insomnia (CBT-I) is highly effective, treatment-associated burdens and limited availability of providers result in few survivors receiving this treatment. To address this gap, we developed the Sleep Treatment Education Program-1 (STEP-1), a single-session intervention addressing insomnia after cancer. As a preliminary evaluation of STEP-1's potential to improve survivors' insomnia, STEP-1 was delivered to a convenience sample of 34 cancer survivors as an educational workshop in person or by videoconference. Participants completed the Insomnia Severity Index (ISI) at the workshop and at 1-month follow-up; items assessing participants' intentions to implement program suggestions and satisfaction were also collected. At 1-month follow-up, mean insomnia symptoms on the ISI were significantly lower compared to baseline (9.73 vs 15.73; d  = 1.38, P  < .001); the reduction in mean ISI scores did not significantly differ between in-person and videoconference participants (5.82 vs 6.33; P  = .78). These results, along with positive indicators of program engagement and satisfaction, support the potential efficacy of STEP-1 to meet survivors' needs for insomnia care. Particularly when delivered by videoconference, STEP-1 has the potential to dramatically improve access and uptake for insomnia treatment in cancer survivors. Results also more generally support development of low-intensity, self-management insomnia interventions for cancer survivors and potentially other populations.